Discourses of gendered identity and representation of women academics in leadership roles in higher education in Pakistan - Lashari, Asadullah (2023)
This study is about discourses related to gendered identity and the representation of women academics in leadership positions in higher education in Pakistan. The literature reviewed showed a global underrepresentation of women in leadership roles and the challenges faced by them. However, few studies have studied discourses on women’s leadership in higher education from multiple participant groups. This study is qualitative in nature. The data was collected through semi-structured interviews from five women leaders, four men and four women academics as well as through two focus groups of four women and four men students. An analytical framework comprising feminist poststructural discourse analysis (FPDA) (Baxter, 2003), Foucault’s (1972; 1975; 1980) notion of regimes of truth, and Bakhtin’s (1981; 1984) notions of heteroglossia and polyglossia, was applied to interpret the data. The key findings of the study indicate that the dominant socio-cultural, religious, and familial regimes of truth are unfavourable for women’s leadership in Pakistan. A majority of participants complied with dominant discourses around women’s leadership identity and their representation in leadership positions including the need for permission and support of family to pursue leadership, the importance of household responsibilities over leadership, the normalisation of workplace harassment and victimisation, and the gender-based division of leadership roles. There were some exceptions among participants’ discourses where they resisted the familial regimes of truth, challenged socio-cultural norms, opposed the gender-based division of leadership and confronted workplace harassment and victimisation. The participants navigated away from gendered regimes of truth in the wider society and in higher education institutions. The study recommends that Provincial and National legislative assemblies, Higher Education Commission Pakistan, and Universities should devise gender equity policies that ensure women’s participation in leadership roles, particularly in important decision-making bodies, e.g., syndicate and senate. Moreover, the study also recommends leadership preparation programmes and networking platforms for aspiring women leaders.